Customer Service Quality as an Implementation of Sharia Banking Legal Policy: A Study on Customer Satisfaction at Bank Syariah Indonesia Padangsidimpuan Branch - Suryadi Syabatullah; Maryam Batubara (Prodi Hukum Ekonomi Syariah, Fakultas Syariah, IAIN Palopo, 2024)
Purpose – This study analyzes the implementation of Sharia Banking Legal Policy in customer service practices and its implications for customer satisfaction at Bank Syariah Indonesia (BSI) Padangsidimpuan Branch. From the perspective of Islamic economic law, sharia banking institutions are legally bound to comply with statutory regulations, Sharia principles, and consumer protection norms. Customer service quality is examined as a socio-legal indicator reflecting how these legal and ethical obligations are operationalized in daily banking interactions. Method – This research adopts a qualitative socio-legal approach focusing on empirical legal practices. Data were obtained through in-depth interviews and direct observations involving ten customers who had recently interacted with customer service officers at BSI KC Padangsidimpuan. Respondents were selected purposively based on their service experience. The analysis employed SERVQUAL dimensions tangibles, reliability, responsiveness, assurance, and empathy to interpret customer perceptions as manifestations of sharia banking legal policy implementation. Result – The findings show that customer service quality at BSI KC Padangsidimpuan is generally perceived positively and contributes to customer satisfaction. Nevertheless, inconsistencies were identified, particularly in responsiveness and interpersonal conduct, indicating partial gaps between normative legal obligations and practical service delivery. These findings suggest that sharia banking legal policy has been implemented, but not yet uniformly realized across all service dimensions. Implication – This study indicates that customer satisfaction functions as a normative outcome of effective sharia banking legal policy implementation rather than a generalized performance measure. Strengthening compliance with Sharia Banking Law, Financial Services Authority (OJK) regulations, and DSN-MUI fatwas especially regarding service ethics, consumer protection, and complaint-handling mechanisms is essential to ensure coherence between Islamic economic law norms and institutional practice. This research contributes to Islamic economic law scholarship by positioning service quality analysis within a qualitative socio-legal framework.